Risk Factors for Poor Adherence to Eyedrops in Electronically Monitored Patients with Glaucoma - Friedman, David S.; Okeke, Constance O.; Jampel, Henry D.; Ying, Gui-shuang; Plyler, Ryan J.; Jiang, Yuzhen; Quigley, Harry A. (Ophthalmology (Rochester, Minn.), 2009)
To identify risk factors for poor adherence to topical once daily therapy for glaucoma. Prospective, observational cohort study. A total of 196 patients with glaucoma who were being treated with a prostaglandin analog in 1 or more eyes at the Scheie or Wilmer Eye Institutes between August 2006 and June 2007. Demographics, ocular history, and responses to interview questions about glaucoma knowledge, health beliefs, and drop-taking behaviors were obtained from each patient. All patients used the Travatan Dosing Aid (DA; Alcon Laboratories Inc., Fort Worth, TX) to administer travoprost as prescribed. Devices were collected at 3 months, and the data of drop use were downloaded using software provided with the DA. Patients taking ≤75% doses during the 8-week period starting 2 weeks after the enrollment visit and ending 2 weeks before the 3-month visit were compared with those taking >75% of doses. Risk factors for poor adherence. Eighty-seven patients (44.4% of the 196 subjects with evaluable data at 3 months) used the DA on 75% or less of the monitored days. In univariate analysis, poorer adherers were more likely to be <50 or ≥80 years of age, to be African American, to report less than excellent health, to report higher amounts of depression, to have lower income, and to be treated at the Scheie Eye Institute. Multivariate analysis (adjusting for education and income) found that age, race/ethnicity, and less than excellent health were associated with poor adherence. Those who failed to take more than 75% of eyedrop doses were more likely to be African American and to report poor health. Those in the youngest and oldest age groups were less adherent, although this finding was not always statistically significant. Further research into the factors driving these associations and into developing predictive models to assist in screening for low adherence are warranted. Proprietary or commercial disclosure may be found after the references.